Spin-Orbit Torques in Transition Metal Dichalcogenide/Ferromagnet Heterostructures - Hidding, Jan; Guimarães, Marcos H. D. (Frontiers in Materials, 2020)
In recent years, there has been a growing interest in spin-orbit torques (SOTs) for manipulating the magnetization in nonvolatile magnetic memory devices. SOTs rely on the spin-orbit coupling of a nonmagnetic material coupled to a ferromagnetic layer to convert an applied charge current into a torque on the magnetization of the ferromagnet (FM). Transition metal dichalcogenides (TMDs) are promising candidates for generating these torques with both high charge-to-spin conversion ratios, and symmetries and directions which are efficient for magnetization manipulation. Moreover, TMDs offer a wide range of attractive properties, such as large spin-orbit coupling, high crystalline quality and diverse crystalline symmetries. Although numerous studies were published on SOTs using TMD/FM heterostructures, we lack clear understanding of the observed SOT symmetries, directions, and strengths. In order to shine some light on the differences and similarities among the works in literature, in this mini-review we compare the results for various TMD/FM devices, highlighting the experimental techniques used to fabricate the devices and to quantify the SOTs, discussing their potential effect on the interface quality and resulting SOTs. This enables us to both identify the impact of particular fabrication steps on the observed SOT symmetries and directions, and give suggestions for their underlying microscopic mechanisms. Furthermore, we highlight recent progress of the theoretical work on SOTs using TMD heterostructures and propose future research directions.